2015
DOI: 10.1111/een.12180
|View full text |Cite
|
Sign up to set email alerts
|

Leaf traits of congeneric host plants explain differences in performance of a specialist herbivore

Abstract: 1. Within the host range of herbivorous insects, performance hierarchies are often correlated with relatedness to a primary host plant, as plant traits are phylogenetically conserved. Therefore, it was hypothesised that differences in herbivore performance on closely related plant species are due to resistance traits that vary in magnitude, rather than in the nature of the traits.2. This hypothesis was tested by manipulating putative resistance traits of three congeneric thistle species (Cirsium arvense, Cirsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 55 publications
1
10
0
1
Order By: Relevance
“…The EICA hypothesis predicts that introduced plant species will be released from native specialist predators, but here we simulated herbivory, which might not accurately represent the effects of specialist herbivores ( Blossey and Notzold, 1995 ). For example, leaf trichome/spine densities have been shown to reduce the performance of a specialized herbivore on Canada thistle ( Cripps et al., 2015 ), but we did not assay variation in leaf trichome/spine densities in our experiment. Alternatively, it might be that tolerance to different stresses in Canada thistle is largely uncoupled from performance, similar to that reported for introduced populations of diffuse knapweed ( Turner et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The EICA hypothesis predicts that introduced plant species will be released from native specialist predators, but here we simulated herbivory, which might not accurately represent the effects of specialist herbivores ( Blossey and Notzold, 1995 ). For example, leaf trichome/spine densities have been shown to reduce the performance of a specialized herbivore on Canada thistle ( Cripps et al., 2015 ), but we did not assay variation in leaf trichome/spine densities in our experiment. Alternatively, it might be that tolerance to different stresses in Canada thistle is largely uncoupled from performance, similar to that reported for introduced populations of diffuse knapweed ( Turner et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This also conferred with our hypothesis that defensive traits, in addition to phylogenetic relationship, affect insect survival. Plant species with high SLA have many features conducive to herbivore feeding, such as lower dry matter, faster growth rate, and reduced leaf toughness ( Salgado-Luarte and Gianoli, 2010 ), and this trait was shown to be an important factor explaining survival of Cassida on plants congeneric to C. arvense ( Cripps et al, 2015 ). The only plant trait found to have a clear phylogenetic signal was leaf pubescence, but this trait was not related to Cassida survival.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that leaf pubescence showed a phylogenetic signal is likely an artifact of low sample size since this trait is common in plant species across the Cardueae subtribes ( Susanna and Garcia-Jacas, 2007 ), and is therefore unlikely to be part of the underlying phylogenetic explanation for Cassida survival. Leaf pubescence is known to provide resistance against most types of insect herbivores, including both generalist and specialist feeders ( Hanley et al, 2007 ), and previously trichome density was found to be an important factor determining survival rates of Cassida on plants congeneric to C. arvense ( Cripps et al, 2015 ). In the present study, leaf pubescence was measured as a proportion of total leaf dry weight and specific pubescence structures that might differently affect Cassida survival were not distinguished.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations